2010
DOI: 10.1007/s00417-010-1432-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes of cornea after ethanol ingestion in Otsuka Long-Evans Tokushima fatty (OLETF) and Long-Evans Tokushima Otsuka (LETO) rats

Abstract: Purpose To compare ethanol-induced ultrastructural changes in corneas of Otsuka Long-Evans Tokushima fatty (OLETF) rats and Long-Evans Tokushima Otsuka (LETO) rats. Methods Forty, five-week-old male LETO and OLETF rats were fed an ethanol-containing liquid diet (LETO alc and OLETF alc) for 11 weeks, and another forty OLETF and LETO rats were put on a pair-fed control diet (LETO con and OLETF con) for 11 weeks. The body weight and fasting blood glucose levels, and 2-hour blood glucose levels after glucose toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Abnormal structure and distribution of the hemidesmosomes of the corneal epithelium are related to reduced epithelial adhesion 12 , 13 and delayed corneal epithelial wound closure. 24 We found that the expression of collagen IV in the corneal epithelial basement membrane was reduced in Col4a3 −/− mice. The ultrastructure of the corneal epithelial basement membrane revealed that the hemidesmosome structure was abnormal in the Col4a3 −/− mice.…”
Section: Discussionmentioning
confidence: 68%
“…Abnormal structure and distribution of the hemidesmosomes of the corneal epithelium are related to reduced epithelial adhesion 12 , 13 and delayed corneal epithelial wound closure. 24 We found that the expression of collagen IV in the corneal epithelial basement membrane was reduced in Col4a3 −/− mice. The ultrastructure of the corneal epithelial basement membrane revealed that the hemidesmosome structure was abnormal in the Col4a3 −/− mice.…”
Section: Discussionmentioning
confidence: 68%
“…Expression of Cytochrome p450 2E1 (CYP2E1) mRNA, CYP2E1 protein activity, and production of reactive oxygen species were determined to be induced by ethanol in a concentration-dependent manner in retinal pigment epithelium [20]. Moreover, chronic alcohol consumption was also associated with the ultra-structural alterations on cornea [21].…”
Section: Discussionmentioning
confidence: 99%
“…Diminished expression of the tight junction proteins including β-catenin and zonula occludens-1 was also observed, indicating the disruption of cell to cell junctions in diabetic cornea 53. Other animal studies showed detrimental effects of hyperglycemia on the corneal epithelium basement membrane complex and demonstrated findings suggesting compromise of corneal epithelial function, such as increase in corneal thickness, disruption of tight junctions, and loss of basal epithelial cells 19,54. The accumulation of AGE in the corneal epithelium basement membrane complex promotes proapoptotic and antiproliferative pathways, which results in corneal epithelial damage 19.…”
Section: Ocular Surface Abnormalities In Dmmentioning
confidence: 99%